2006
DOI: 10.1536/ihj.47.901
|View full text |Cite
|
Sign up to set email alerts
|

<b>Downregulation of Peroxisme Proliferator Activated Receptor Gamma Co-Activator 1&alpha; in Diabetic Rats</b>

Abstract: SUMMARYDiabetes mellitus (DM), which induces alterations in energy metabolism, is the leading cause of cardiovascular disease. We postulated that peroxisome proliferator activated receptor-γ coactivator 1α (PGC-α), a transcriptional coactivator that is the primary regulator of oxidative metabolism and mitochondrial biogenesis, and cardiac function are depressive in DM and simvastatin and losartan therapy can improve the affects of DM on mRNA expression of PGC-1α and cardiac function. An experimental model of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…Consistently, DM has been found to induce suppression of mRNA expression of PGC-1α and deterioration of LV function in diabetic rats. 30) Therefore, our findings and those from previous studies 22,30,32) may explain the suppression of LV function in poorly controlled hyperglycemic rats.…”
Section: 7)supporting
confidence: 69%
See 1 more Smart Citation
“…Consistently, DM has been found to induce suppression of mRNA expression of PGC-1α and deterioration of LV function in diabetic rats. 30) Therefore, our findings and those from previous studies 22,30,32) may explain the suppression of LV function in poorly controlled hyperglycemic rats.…”
Section: 7)supporting
confidence: 69%
“…The procedure and protocol were described in detail in a previous recent report. 30) Procedure and protocol for measurement of reactive oxygen species (ROS): 2',7'-Dichlorodihydrofluorescin diacetate (H 2 DCFDA, Molecular Probes) was dissolved in DMSO at a concentration of 25 mg/mL. After being diluted with 50% ethanol to a final concentration of 2.5 mg/mL, 6 μg per gram of rat body weight was administered to the dorsal vein of the penis immediately following echocardiographic examination as modified from a method previously described.…”
mentioning
confidence: 99%
“…10) Interestingly, our recent studies have also shown that PGC-1α gene expression is significantly reduced in DM rats with LV dysfunction and in rats with acute myocardial infarction (AMI). 11,12) In the present study, one of the important findings was that PGC-1α gene expression was remarkably suppressed in DCM rats. Moreover, the cytochrome C level in mitochondria was also markedly decreased in the DCM rats.…”
Section: Discussionsupporting
confidence: 47%
“…Our findings, therefore, corroborate those of previous experimental studies. [10][11][12] Of interest in the present study is that losartan was comparable to carvedilol in preserving LV function and cytochrome C levels in mitochondria. Additionally, losartan was found to be superior to carvedilol in inhibiting PGC-1α gene down-regulation in induced DCM.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation